Beamline and Flight Comparisons of the ARMAS Flight Module With the Tissue Equivalent Proportional Counter for Improving Atmospheric Radiation Monitoring Accuracy - Brad “Buddy” Gersey; W. Kent Tobiska; William Atwell; Dave Bouwer; Leonid Didkovsky; Kevin Judge; Seth Wieman; Richard Wilkins (Space Weather, 2020)
Abstract Ionizing radiation at aircraft and commercial suborbital spaceflight altitudes is driven by space weather and is a health concern for crew and passengers. We compare the response functions of two radiation detectors that were exposed to four different ground‐based laboratory radiation fields as well as flown alongside each other on aircraft. The detectors were a tissue equivalent proportional counter (TEPC) and a Teledyne silicon micro dosimeter chip that was integrated into an Automated Radiation Measurements for Aerospace Safety Flight Module (ARMAS FM). Both detectors were flown onboard commercial and research aircraft. In addition, both detectors were exposed neutrons at the Los Alamos Neutron Science Center, protons at Loma Linda University Medical Center, 56Fe particles at the NASA Space Radiation Laboratory, and also a gamma radiation source at Lawrence Livermore National Laboratory. The response of each of these instruments as well as derived dosimetric quantities are compared for each radiation exposure and the ratio for converting ARMAS absorbed dose in silicon to an estimated absorbed dose in tissue is obtained. This process resulted in the first definitive calibration of the silicon‐based detector like ARMAS to TEPC. In particular, with seven flights of both instruments together, the ARMAS‐derived dose in tissue was then validated with the TEPC‐measured dose in tissue and these results are reported. This work provides a method for significantly improving the accuracy of radiation measurements relevant to human tissue safety using a silicon detector that is easy to deploy and can report data in real time.